Ta’zir-Based Pedagogical Punishment for Character Formation and Moral Development in Muslim Educational Institutions - Asrofi Tiktana; Azam Syukur Rahmatullah (JIE (Journal of Islamic Education), 2026)
This study investigates the empirical relationship between the implementation of ta’zir-based disciplinary practices and student moral character development in Muslim educational institutions in Yogyakarta, Indonesia, addressing a significant gap between classical Islamic educational theory and contemporary empirical research. A quantitative correlational survey design was employed with 387 respondents drawn through stratified random sampling from pesantren and madrasah settings, comprising students, PAI teachers, and administrators. Data were analysed using multiple linear regression via IBM SPSS Statistics version 26. Research results show the four sub-dimensions of ta’zir implementation collectively explained 61.0% of variance in moral character development (R² = 0.610, F = 148.73, p = 0.000), indicating a strong and statistically significant relationship between ta’zir practices and students' moral formation. Teacher-student relational context emerged as the strongest predictor (β = 0.312), meaning the quality of the pedagogical relationship most decisively shapes the effectiveness of disciplinary intervention, followed by educative intentionality (β = 0.263), graduated corrective approach (β = 0.228), and proportionality (β = 0.187), each reflecting that disciplinary practices grounded in educational purpose, gradual correction, and fairness contribute meaningfully to students' moral character development. Findings are geographically restricted to Yogyakarta and limited by cross-sectional design and self-report instrumentation. This study offers the first empirically validated four-dimensional framework for ta’zir implementation, demonstrating that principled Islamic disciplinary practice constitutes a measurable mechanism of moral formation, with significant implications for teacher development and institutional policy in Muslim educational contexts globally.